2022
DOI: 10.3389/fcvm.2022.912999
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Metabolic Syndrome in Patients With Non-ST Elevated Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: ObjectiveWe aim to investigate the prognostic effects of metabolic syndrome (MS) on patients with non-ST elevated myocardial infarction (NSTEMI) after percutaneous coronary intervention (PCI).MethodsPatients with NSTEMI undergoing PCI were consecutively collected. According to the presence or absence of MS, they were divided into two groups and followed up for 1 year. The endpoint was major adverse cardiovascular events (MACE), including all-cause death, unstable angina hospitalization, heart failure (HF) hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…[9,19–22] In Taiwan, Li-Hong Zhao et al (2022) reported a prevalence of MetS of 50.9%. [13] Similarly, Lee et al reported a 59.40% prevalence of ST-elevation AMI in South Korea. [23] These findings suggest that MetS is a common occurrence in the population of coronary artery disease patients, particularly among those with AMI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[9,19–22] In Taiwan, Li-Hong Zhao et al (2022) reported a prevalence of MetS of 50.9%. [13] Similarly, Lee et al reported a 59.40% prevalence of ST-elevation AMI in South Korea. [23] These findings suggest that MetS is a common occurrence in the population of coronary artery disease patients, particularly among those with AMI.…”
Section: Discussionmentioning
confidence: 97%
“…[10,11] Until around 20 years ago, the prevalence of MetS in Asian countries was low compared with that in Western countries. [12,13] A comprehensive meta-analysis of 87 studies involving 951,083 patients demonstrated that MetS is associated with a 2-fold increase in cardiovascular mortality, AMI, and stroke, and a 1.5-fold increase in all-cause mortality risk. [14] Most of these studies were carried out in developed countries among patients with ACS who were managed differently, and this likely affected their prognosis and the likelihood of new adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were reported in Non-ST-elevation myocardial infarction, where patients with a BMI of ≥28 kg/m 2 had a more adverse outcome and the occurrence of MACE. It was concluded that controlling abdominal obesity might improve the prognosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…1. Consequently, the meta-analysis included 10 observational studies [19][20][21][22][23][24][25][26][27][28].…”
Section: Study Retrievalmentioning
confidence: 99%
“…These studies were performed in Italy, Japan, Korea, Serbia, and China, and published between 2005 and 2022. As for study design, five studies were prospective cohort studies [21,23,25,27,28], four were retrospective cohort [20,22,24,26], and another one was post-hoc analysis of a clinical trial [19]. All the studies included patients with MI (total sample size: 33 197), with mean age of the patients varying from 41 to 71 years.…”
Section: Study Characteristicsmentioning
confidence: 99%